2007
DOI: 10.1091/mbc.e07-02-0185
|View full text |Cite
|
Sign up to set email alerts
|

Dual Mechanism of a Natural CaMKII Inhibitor

Abstract: Ca 2؉ /calmodulin (CaM)-dependent protein kinase II (CaMKII) is a major mediator of cellular Ca 2؉ signaling. Several inhibitors are commonly used to study CaMKII function, but these inhibitors all lack specificity. CaM-KIIN is a natural, specific CaMKII inhibitor protein. CN21 (derived from CaM-KIIN amino acids 43-63) showed full specificity and potency of CaMKII inhibition. CNs completely blocked Ca 2؉ -stimulated and autonomous substrate phosphorylation by CaMKII and autophosphorylation at T305. However, T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
285
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(295 citation statements)
references
References 76 publications
9
285
1
Order By: Relevance
“…Specifically, CaMKII could be involved in the organization of a structural link at the PSD (Lisman et al, 2002) and spine cytoskeleton (Narayanan et al, 2006) necessary to stabilize AMPARs at the synapse. Consistent with this notion, recent data directly demonstrated that an inhibitor that interferes with CaMKII binding to NR2B subunit (Vest et al, 2007) significantly suppresses basal synaptic transmission (Sanhueza et al, 2007).…”
Section: Camkii Content and Postsynaptic Strengthmentioning
confidence: 60%
“…Specifically, CaMKII could be involved in the organization of a structural link at the PSD (Lisman et al, 2002) and spine cytoskeleton (Narayanan et al, 2006) necessary to stabilize AMPARs at the synapse. Consistent with this notion, recent data directly demonstrated that an inhibitor that interferes with CaMKII binding to NR2B subunit (Vest et al, 2007) significantly suppresses basal synaptic transmission (Sanhueza et al, 2007).…”
Section: Camkii Content and Postsynaptic Strengthmentioning
confidence: 60%
“…To evaluate drug interferes competitively with CaMKII/CaM binding, and thus, it is ineffective on the autonomous activity of the kinase. 17 …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, siRNA only reduced the global cellular CaMKII activity (not shown), while antCaNtide and the CaMKII dominant-negative mutant (K42M, used in subsequent experiments) are recognized as the most specific and potent inhibitors. 17 AntCaNtide pretreatment reduced FCSinduced ERK phosphorylation in a dose-dependent manner. In parallel, ERK phosphorylation induced by KRas V12 was inhibited by antCaNtide treatment.…”
Section: Introductionmentioning
confidence: 83%
“…A region of the CaMKII␣ catalytic domain, termed the T-site by Bayer, Schulman, and co-workers, appears to be critical for binding to CaMKIIN, GluN2B, and the CaMKII autoinhibitory domain (23,24,27,28). The role of the T-site in interactions of constitutively active and mCherry-tagged T287D-CaMKII␤ mutant with the densin-IN domain was investigated by mutating Ile-206 and Asp-239 to Lys and Arg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…N-tide, a peptide analog containing residues 43-69 of CaMKIIN (26) (termed CN27 by Vest et al (27)), competes with densin-IN for binding CaMKII in vitro. In a crystal structure of CaMKII bound to an N-tide variant (44), amino acid side chains in the N-terminal and central regions of N-tide (underlined in Fig.…”
Section: Discussionmentioning
confidence: 99%